The Ethical Dilemma of Tooth Extraction on Patient Request [Letter] - Fayaz Y; Ahmadi SU; Miri SAS (Dove Medical Press, 2024)
Yahya Fayaz,1 Shahab Uddin Ahmadi,1 Said Ahmad Sorosh Miri2 1Department of Stomatology, Khatam AL Nabieen University, Kabul, Afghanistan; 2Department of Prosthodontics, Khatam AL Nabieen University, Kabul, AfghanistanCorrespondence: Yahya Fayaz, Department of Stomatology, Khatam AL Nabieen University, Kabul, Afghanistan, Tel +93 (0) 706281798, Email dr.yahyafayaz@gmail.com